GROPIUS - bauhaus. - Cassiani Ingoni, Paolo (Como : Pantha Arte, 1980)
tentoonstelling in Como, Italië, februari 1980
Adlib record nr. 530002559
Italiaans
boek
Keywords: Gropius, Walter; modernisme; Duitsland